Photocatalytic degradation of Congo red and methylene blue dyes and antibacterial activity using silver nanoparticles synthesized from Aqueous Seeds Extract of Ziziphus Spina-Christi - Mohamed Erhayem (The Libyan Journal of Science, 2024)
In the present study, silver nanoparticles (Ag-NPs) was used as catalyst for the photo degradation of Congo Red dye, CR, and Methylene Blue dye, MB under UV-light have wavelength of 254 nm and irradiation time of 120 min. In addition, The antibacterial activity of Ag-NPs was studied on Staphylococcus aureus as Gram-positive and E.coli as Gram-negative bacteria. The photocatalytic degradation efficiency was 87.11% for CR, and was 86.46% for MB. The kinetic of photocatalytic degradation of CR and MB dyes belonged to second order model with coefficient of correlation (R2) equals 0.973 and 0.998, respectively. The rate constants of second order model of CR and MB dyes was noted to be equals 198 L.mol-1.min-1, 5555 L.mol-1.min-1. The half-life of second order model of CR and MB dyes was found to be equals 17.8 and 12.6 minutes for CR and MB dyes, respectively. The antibacterial activity of the nanoparticles was studied. Gram- positive bacteria showed minimum zone of inhibition at 17.9 and Gram-negative bacteria was showed maximum zone of inhibition at 22.3 mm.